Association mapping of the PARK10 region for Parkinson’s disease susceptibility genes - Wan, Jia Y. (2013)
BACKGROUND: Previous studies indicate that as many as six genes within the PARK10 region (RNF11, UQCRH, HIVEP3, EIF2B3, USP24, ELAVL4) might modify susceptibility or age at onset in Parkinson’s disease (PD). METHODS: We sought to identify new PD susceptibility genes and to validate previously nominated candidate genes within the PARK10 region using a two-stage design. We used data from a large, publicly-available genome-wide association study (GWAS) in the discovery stage (n=2000 cases and 1986 controls) and data from three independent studies for the replication stage (total n=2113 cases and 2095 controls). Marker density was increased by imputation using HapMap3 and 1000 Genomes reference panels, and over 40,000 single nucleotide polymorphisms (SNPs) were used in the final analysis. The association between each SNP and PD was modeled using logistic regression with an additive allele dosage effect and adjusted for sex, age, and axes of geographical variation. RESULTS: Although the discovery stage yielded promising findings for SNPs in several novel genes, including DAB1, none of the results were validated in the replication stage. Furthermore, in meta-analyses across all datasets no genes within PARK10 reached significance after accounting for multiple testing. CONCLUSION: Our results suggest that common variation in the PARK10 region is not associated with PD risk. However, additional studies are needed to assess the role of PARK10 in modifying age at onset and to determine whether rare variants in this region might affect PD susceptibility.